Description of Bullying Behavior in Learning in Elementary School Upgrade Students - Jumrizal, Jumrizal; Yulia, Yuyun; Cahyani, Berliana Henu (Postgraduate School, Universitas Negeri Padang, 2023)
Bullying behavior in Senior High School (SHS) and Elementary School (ES) classes is one of the serious problems that still often occurs in the learning process. Bullying behavior harms students, such as preventing students from participating in the learning process and having difficulty socializing with classmates. The purpose of this study was conducted to provide a real picture of bullying behavior by ES seniors. This study uses a qualitative method with a case study approach. The research subjects were students with an average age of 9-11 years. Then the sampling using a purposive random sampling technique. Participants in this study were 6 children, where 3 participants represented victims of bullying and 3 others represented perpetrators of bullying. Then the data collection technique from the research conducted was through observation and reinforced by interviews with 3 teachers as informants where each teacher represented one student who was bullying and one student who was a victim of bullying. The results of the study showed that there were students who became victims of bullying behavior and were victims of bullying in the three forms of bullying behavior that occurred, namely physical, verbal, and psychological bullying behavior.